APLIKASI STEMMING BAHASA JAWA (Information Technology and Telematics, 2014)
AbstractStemming the Java language is an information system that produces a word basic information entered by the user in the form. This system is part of a management information system, which was developed to collect, process into the data base word in the Java language, so that data can be retrieved to be distributed as a useful information.The realization of this system development is the creation of applications that use the Java language stemming algorithms porter and the PHP programming language. So the authors make stemming the Java language that is able to enter the Java language input and display word information basicword stemming results.In conducting the analysis and design of stemming the Java language, the author uses the method of prototyping systems development. Meanwhile, to make the process of analysis, the authors used a method of analysis abbot. The authors use design tool consisting of a flowchart and diagram easy case. From the analysis and design, systems stemming generated anew web-based Java language that can be used in finding the basic Java language.Keywords : Porter Stemming , Java Language ,BasicWord: